2017
DOI: 10.3390/en10091337
|View full text |Cite
|
Sign up to set email alerts
|

Flame Front Propagation in an Optical GDI Engine under Stoichiometric and Lean Burn Conditions

Abstract: Lean fueling of spark ignited (SI) engines is a valid method for increasing efficiency and reducing nitric oxide (NO x ) emissions. Gasoline direct injection (GDI) allows better fuel economy with respect to the port-fuel injection configuration, through greater flexibility to load changes, reduced tendency to abnormal combustion, and reduction of pumping and heat losses. During homogenous charge operation with lean mixtures, flame development is prolonged and incomplete combustion can even occur, causing a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…It is important to note that pressure was directly taken from the pressure transducer. Meanwhile, the temperature was estimated with the first law of thermodynamics coupled with a heat and mass transfer model [34]. The results show the same trend between fuels in laminar and turbulent flame speed.…”
Section: Optical Investigationsmentioning
confidence: 84%
See 2 more Smart Citations
“…It is important to note that pressure was directly taken from the pressure transducer. Meanwhile, the temperature was estimated with the first law of thermodynamics coupled with a heat and mass transfer model [34]. The results show the same trend between fuels in laminar and turbulent flame speed.…”
Section: Optical Investigationsmentioning
confidence: 84%
“…Two different setups were used, one for high-luminosity flames (methane and pure syngas at λ = 1.0) with f/32 and the other with f/5.6 for diluted syngas and lean methane combustion. In spite of the fact that this approach has the disadvantage that flame luminosity between mixtures cannot be quantitatively compared, it avoids the risk of damage to the equipment and has no effect on the analysis of flame morphology parameters [34].…”
Section: Thermodynamic and Optical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez et al [19] studied the flame front propagation in an optical GDI engine under stoichiometric and lean burn conditions using cycle resolved digital imaging. The data was first exported as 8-bit grey-level images and pre-processed to adjust the contrast and brightness with respect to the maximum intensity value.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a potential alternative is the mix of both concepts to achieve a stable combustion process, with low particle emission and without losing performance. Some authors have studied this strategy of homogeneous in-cylinder charge with single [16,17], and multiple injections [18][19][20] in the intake and early compression stroke. Marseglia et al [18] found that the split injection strategy introduces positive effects with respect to the single injection case, such as the reduction of coefficient of variation of the indicate mean effective pressure (COVIMEP), tendency to knock, carbon monoxide emissions, as well as soot formation.…”
Section: Introductionmentioning
confidence: 99%